DETERMINASI SOSIAL LINGKUNGAN KERJA DAN EPIDEMIOLOGI MANAJERIAL: TINJAUAN LITERATUR DAMPAK PELATIHAN DAN PENGEMBANGAN KARIR TERHADAP MOTIVASI KERJA MELALUI MEDIASI KEPUASAN KERJA DI RSUD PROVINSI NTB - Susi Wirawati Triyono; Yuly Peristiowati (Jurnal Cakrawala Ilmiah, 2026)
Background: Employee work motivation in the health sector, particularly at RSUD NTB Province, is a crucial determinant in ensuring service quality and patient safety. However, fluctuations in motivation are often managerial challenges influenced by human resource development policies. Objective: This study aims to analyze and synthesize literature regarding the influence of training and career development on work motivation and to examine the mediating role of job satisfaction in this relationship through a managerial epidemiology perspective. Methods: This study uses the Systematic Literature Review (SLR) method. The literature search was conducted through Google Scholar and Scopus databases with a publication timeframe of 2014-2024. Inclusion criteria focused on original research discussing the variables of training, career, satisfaction, and motivation in health organizations or public services. Results: The review results show that training and career development have a significant positive impact on work motivation. The main findings confirm that job satisfaction functions as an essential mediator; meaning that training programs and career path clarity will only optimally increase motivation if they can meet expectations and provide psychological satisfaction for employees. Conclusion: Epidemiologically, job satisfaction acts as an intermediate factor that determines organizational health. The management of RSUD NTB Province is advised to integrate competency development programs with transparent career systems to mitigate the risk of declining work motivation.